2021
DOI: 10.1002/adfm.202103353
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Doping of 2D Indium Selenide for Ultrahigh Performance and Low‐Power Consumption Broadband Photodetectors

Abstract: Two-dimensional (2D) photodetecting materials have shown superior performances over traditional materials (e.g., silicon, perylenes), which demonstrate low responsivity (R) (<1 AW −1 ), external quantum efficiency (EQE) (<100%), and limited detection bandwidth. Recently, 2D indium selenide (InSe) emerged as high-performance active material in field-effect transistors and photodetectors, whose fabrication required expensive and complex techniques. Here, it is shown for the first time how molecular functionaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Also, response speed is still another critical parameter toward photodetector, [ 42 ] since it reflects the capacity of device for capturing optical signals in speed. Figure S7c, Supporting Information depicts the photodetector's rapid response to 650 nm pulsed light at frequency of 10 kHz, revealing that our photodetector has outstanding on‐off switching characteristics, excellent repeatability and a rapid response speed.…”
Section: Resultsmentioning
confidence: 99%
“…Also, response speed is still another critical parameter toward photodetector, [ 42 ] since it reflects the capacity of device for capturing optical signals in speed. Figure S7c, Supporting Information depicts the photodetector's rapid response to 650 nm pulsed light at frequency of 10 kHz, revealing that our photodetector has outstanding on‐off switching characteristics, excellent repeatability and a rapid response speed.…”
Section: Resultsmentioning
confidence: 99%
“…The nonlinear light power dependence is the result of complex processes in the photoresponse, including electron–hole generation, trapping, and photocarriers recombination. [ 31 ] The sublinear light power‐dependent behavior (α < 1) implies a new route for photoexcited carriers through recombination loss, which has been reported in other materials, such as in MoS 2 , [ 32–34 ] InSe, [ 35 ] ZnO nanowires, [ 36 ] GaN nanowires, [ 37 ] and Germanium nanowires. [ 38 ] However, the superlinear dependence behavior (α > 1) was observed in monolayer MoS 2(1‐x) Se 2x [ 39 ] and Ta 2 NiSe 5 [ 40 ] (α = 1.1), which are relatively rare compared with sublinear and linear light power dependence.…”
Section: Resultsmentioning
confidence: 96%
“…Li et al [54] reported a design that introduces an interfacial oxide layer between the graphene and n-silicon; the dark current of graphene/n-Si heterojunction has been reduced by two orders of magnitude at zero bias. At room temperature, the graphene/n-Si photodetector with interfacial oxide exhibits a specific detectivity up to 5.77 × 10 13 Jones with a responsivity of 0.73 A W −1 as well as a high on/off ratio of ~10 7 . Fig.…”
Section: The Improvements For Graphene-based Devicesmentioning
confidence: 99%
“…In addition to in-depth investigations on graphene, not only a large number of new low-dimensional materials have been discovered, but the old bulk materials have been injected with new vitality. Research in recent years has shown that low-dimensional materials possess many unprecedented merits, such as strong light-matter coupling [2], adjustable bandgap [3], high carrier mobility [4], low dark current [5], appreciable signal-to-noise ratio [6], ultra-low energy dissipation [7], and fast response/recover speed [8]. These advantages have made low-dimensional materials potential to outperform traditional 3D bulk materials in the next generation of optoelectronics.…”
Section: Introductionmentioning
confidence: 99%